2016
DOI: 10.5846/stxb201501300251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exclosure duration on the community structure and species diversity of an alpine meadow in the Qinghai-Tibet Plateau

Abstract: 收稿日期:2015• 01• 30; 网络出版日期:2015• 00• 00 * 通讯作者 Corresponding author.E•mail: songgu@ nankai.edu.cn DOI: 10.5846 / stxb201501300251 刘晓琴,张翔,张立锋,李英年,赵亮,徐世晓,李红琴,马荣荣,牛犇,高玉葆,古松.封育年限对高寒草甸群落组分和物种多样性的影响.生态学报, 2016,36(16) : • . Liu X Q, Zhang X, Zhang L F, Li Y N, Zhao L, Xu S X, Li H Q, Ma R R, Niu B, Gao Y B, Gu S.Effects of exclosure duration on the community structure and species diversity of an alpine meadow in the Qinghai•Tibet Plateau.Acta Ecologica Sinica,2016,36(16) : • .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For instance, Shannon diversity of plants increased along the secondary succession from abandoned agricultural lands to forest in Mediterranean semi-arid regions (Heydari et al, 2020). Yet a decline in taxonomic diversity happened during grassland restoration on the Qinghai-Tibet Plateau, due to the inhibition of litter coverage time on seedling emergence and establishment (Liu et al, 2016). We found that the species evenness strengthened during succession, but the diversity and dominance indices changed negligibly with stand age (Figure 2).…”
Section: Shifts In Biodiversity During Successionmentioning
confidence: 79%
“…For instance, Shannon diversity of plants increased along the secondary succession from abandoned agricultural lands to forest in Mediterranean semi-arid regions (Heydari et al, 2020). Yet a decline in taxonomic diversity happened during grassland restoration on the Qinghai-Tibet Plateau, due to the inhibition of litter coverage time on seedling emergence and establishment (Liu et al, 2016). We found that the species evenness strengthened during succession, but the diversity and dominance indices changed negligibly with stand age (Figure 2).…”
Section: Shifts In Biodiversity During Successionmentioning
confidence: 79%